Devastating Outcome of Late Onset Preeclampsia in a Multiparous Woman: A Case Report - Khatiwada, Sindhu; Nepal, Muna (Journal of BP Koirala Institute of Health Sciences, 2021)
Late onset preeclampsia may occur nascently in a multiparous woman. Although, early onset preeclampsia is associated with more adverse maternal and perinatal outcomes, late onset type in a multiparous woman can occur unexpectedly, and may progress rapidly to a life threatening situation. We report a case of late onset preeclampsia with HELLP syndrome and intracranial haemorrhage in a multiparous woman, who succumbed to death during the course of her treatment. We conclude that preeclampsia is a potential threat for dreadful outcomes, irrespective of its type, parity and duration of onset.